Effects of the different Tai Chi exercise cycles on patients with essential hypertension: A systematic review and meta-analysis - Yin, Yikun; Yu, Zhengze; Wang, Jialin; Sun, Junzhi (Frontiers in Cardiovascular Medicine, 2023)
Objective The main treatment for essential hypertension at this stage is pharmacotherapy. Long-term pharmacotherapy is costly with some side effects. Tai Chi, a bright star in traditional Chinese arts, relaxes both mind and body and has been shown to relax blood vessels and lower blood pressure. This study aimed to systematically review the therapeutic effectiveness of the Tai Chi exercise cycle on blood pressure and cardiovascular risk factors of patients with essential hypertension. Methods Searching CNKI, VIP, CBM, PubMed, EBSCO, Embase, Cochrane Library, and Web of Science to collect randomized controlled trials about Tai Chi exercise in the treatment of patients with essential hypertension according to the inclusion and exclusion criteria. The search time ranged from the date of database construction to December 2022. The Cochrane risk-of-bias tool was used to evaluate the included trials. The meta-analysis was performed with RevMan5.3 and Stata12.0 software. Results According to the meta-analysis, compared with the controls, Tai Chi exercise with a cycle of more than 12 weeks may be better for the reduction of systolic blood pressure (SBP) [MD = −11.72, 95% CI (−15.52, −7.91)] and diastolic blood pressure (DBP) [MD = −4.68, 95% CI (−7.23, −2.12)], as well as increasing the content of nitric oxide (NO) [MD = 0.99, 95% CI (0.69, 1.28)]. The blood lipid metabolism ability may also be improved after more than 12 weeks of Tai Chi exercise, total cholesterol (TC) [SMD = −0.68, 95% CI (−0.89, −0.46), triglyceride (TG) [SMD = −0.84, 95% CI (−1.25, −0.43)], low-density lipoprotein cholesterol (LDL-C) [SMD = −1.58, 95% CI (−2.29, −0.86)]. However, the improvement of high-density lipoprotein cholesterol (HDL-C) [SMD = 0.54, 95% CI (0.28, 0.79)] was better with a less than 12 weeks exercise cycle. A subgroup analysis for exercise frequency and time showed that the exercise frequency should preferably be more than or equal to 5 times per week for patients with hypertension, and for patients with hypertension plus hyperlipidemia, the exercise frequency less than 5 times per week with exercise time less than 60 min each day may be more beneficial. Conclusion The meta-analysis indicated that a more than 12 weeks Tai Chi exercise cycle with less than 60 min each time and more than 5 times per week may be more beneficial in blood pressure reduction, NO level increasing and blood lipid metabolism improving in the comparison with the other exercise cycles. For patients with hypertension plus hyperlipidemia, exercise frequency of less than 5 times per week may be better. Systematic Review Registration [http://www.crd.york.ac.uk/prospero], identifier [CRD42022352035].